War and children's aggressive and prosocial behavior - Žužul, Miomir (Array, 1992)
The aim of this study was to examine whether and how extreme environmental influences such as war could affect the development of the child's aggressive and prosocial behavior. In a combined longitudinal-transversal study design aggressive and prosocial behaviour of pre-school children aged 5 and 6 years was examined. Preschool teachers assessed children's behavior on the Scale of aggressive and prosocial behavior (Žužul and Vlahovic-Štetić, 1990) before the war (1991) and after the biggest acts of war in Croatia (1992). Age differences as well as the differences in children's prosocial and aggressive behaviour during the observed period are examined.